Bernhard Lang: Critical Guides to Contemporary Composers - Dysers, Christine (Critical Guides to Contemporary Composers, 2023)
Bernhard Lang: Critical Guides to Contemporary Composers offers a critical guide and introduction to the work of Austrian composer Bernhard Lang (b. 1957). It identifies the phenomenon of repetition as a central concern in Lang's thinking and making. The composer's artistic practice is identified as one of 'loop aesthetics': a creative poetics in which repetition serves not only as methodology, but also as material, language, and subject matter. The book is structured around the four central thematic nodes of philosophy, music, theatre, and politics. After introducing Lang as a composer whose work is thoroughly influenced by philosophical thought, the book develops a typology of musical repetition as it is explored and activated in Lang's oeuvre. Pointing towards the several repetitions within the performance of Lang's works, the book explores the heavily trans-medial nature of the repeat across domains such as literature, dance, and theatre. Finally, the book investigates Lang's use of textual quotation and musical borrowing. Christine Dysers is a musicologist specialising in contemporary music aesthetics. Her research centres around repetition, politics, absence, the liminal, and the uncanny. This is the first full-length study of the works of Bernhard Lang and is a new volume in the Critical Guides to Contemporary Composers series from Intellect.